Development and validation of a short form psychometric tool assessing the caregiving Challenge of Living with Cystic Fibrosis (CLCF-SF) in a child. - McCray, Gareth; Hope, Holly F.; Glasscoe, Claire; Hill, Jonathan; Quittner, Alexandra; Southern, Kevin W.; Lancaster, Gillian A. (Psychology & Health, 2025)
Objective: Caring for a child with cystic fibrosis (CF) is a rigorous daily commitment for caregivers and treatment burden is a major concern. We aimed to develop and validate a short form version of a 46-item tool assessing the Challenge of Living with Cystic Fibrosis (CLCF) for clinical or research use. Design: A novel genetic algorithm based on 'evolving' a subset of items from a pre-specified set of criteria, was applied to optimise the tool, using data from 135 families. Main outcome measures: Internal reliability and validity were assessed; the latter compared scores to validated tests of parental well-being, markers of treatment burden, and disease severity. Results: The 15-item CLCF-SF demonstrated very good internal consistency [Cronbach's alpha 0.82 (95%CI 0.78–0.87)]. Scores for convergent validity correlated with the Beck Depression Inventory (Rho = 0.48), State Trait Anxiety Inventory (STAI-State, Rho = 0.41; STAI-Trait, Rho = 0.43), Cystic Fibrosis Questionnaire-Revised, lung function (Rho = −0.37), caregiver treatment management (r = 0.48) and child treatment management (r = 0.45), and discriminated between unwell and well children with CF (Mean Difference 5.5, 95%CI 2.5–8.5, p < 0.001), and recent or no hospital admission (MD 3.6, 95%CI 0.25–6.95, p = 0.039). Conclusion: The CLCF-SF provides a robust 15-item tool for assessing the challenge of living with a child with CF.